Discourse the basics - Goddard, Angela 1954-; Carey, Neil (Routledge, Taylor & Francis Group, 2017)
Humans are social animals and through conversation, written communication, symbols and other expressions are constantly interacting with each other. 'Discourse' is an accessible and engaging introduction to the analysis of those interactions and the many forms, expressions and meanings they can take. The book draws on a range of international case studies and examples from literature, political speech, advertising and newspaper articles to address key questions such as: What is discourse? Why are there different approaches to understanding discourse? What issues affect the collection and management of discourse? How can discourse be represented?